Pengaruh Pemberian Pupuk Bokashi Feses Ayam Dan Daun Kirinyuh Dengan Level Yang Berbeda (0, 15, 30 Dan 45 Ton/Ha) Terhadap Pertambahan Panjang Daun, Produksi Berat Segar, Dan Komposisi Fraksi Serat Pada Pertumbuhan Ketiga Rumput Odot - Limu, Aldy May; Sudarma, I Made Adi (Universitas Kristen Wira Wacana Sumba, 2024)
This research aims to see the increase in leaf length and fresh weight production as well as the fiber fraction content in odot grass plants given chicken feces bokashi fertilizer and kirinyuh leaves in each bed plot at different levels. The research was conducted in Kuta Village, Kanatang District, East Sumba Regency. The main research material used was odot grass cuttings, with soil beds and using chicken feces bokashi fertilizer. The experimental design used was a Completely Randomized Design (CRD) with 4 treatments and 4 replications where each replication consisted of 9 odot grass seedlings/cuttings so that there were a total of 144 experimental units. Treatment P0: no fertilizer (control); P1: fertilizer application 15 tons/ha; P2: fertilizer application 30 tons/ha; P3: fertilizer application 45 tons/ha. The results of the study showed that the application of chicken feces bokashi and kirinyuh fertilizer at doses of 0, 15, 30 and 45 tons/ha in the second week had an effect on leaf length growth, but in the fourth to the eighth week it had no real effect because it was most likely The effect is reduced availability of nutrients in the soil. The fresh weight production results of odot grass had a significant effect on the fertilizer treatment compared to without fertilizer where P3 (923.75g) gave the best results compared to all treatments. Meanwhile, the analysis of fiber content shows that the value for each fiber fraction is good with an average NDF (76.274%); ADF (43,915); Cellulose (30,696); Lignin (3,419); Hemicellulose (32,359); and Silica (0.578). It can be concluded that by administering chicken feces bokashi fertilizer at a level of 45 tons/ha, it is still able to provide the best results for growth and third harvest of odot grass plants.